New data on the ontogeny and senescence of Desmostylus (Desmostylia, Mammalia). Issue 2 (3rd March 2016) - Santos, Gabriel-Philip; Parham, James F.; Beatty, Brian L.
ABSTRACT: Ontogenetic sequence and life stage determination among the desmostylians are poorly understood and known mostly from the study of dental eruption. Advanced-age life stages are nearly unknown. New material of an individual Desmostylus from the late middle to late Miocene of Orange County, California, represents the most ontogenetically advanced described specimen of the genus and helps characterize a more complete ontogenetic sequence. The material consists of a partial mandible that exhibits bony swellings, indicative of Desmostylus, but also lacks postcanine teeth (dental senescence). Comparisons with known juvenile Desmostylus and adult-stage individuals with similar bony swellings, but that still exhibit postcanine teeth, provide evidence that the Orange County specimen is that of an elderly Desmostylus . By incorporating the characteristics of this specimen into the ontogenetic sequence of the genus, a complete eruption pattern of the lower jaw can be recreated. The development of the mandible and tooth eruption sequence in Desmostylus is similar to the characteristic ontogeny of Afrotheria. In Afrotheria, the eruption of the final set of molars is delayed until the mandible has grown to maximum length. Desmostylia has been placed in Afrotheria, suggesting that the similarities in ontogenetic sequences may derive from a shared ancestry. Recent studies that place Desmostylia as stem perissodactyls suggest that the Afrotheria-like dental ontogeny may be independently derived within Desmostylia, or Desmostylus . Citation for this article: Santos, G.-P., J. F. Parham, and B. L. Beatty. 2016. New data on the ontogeny and senescence of Desmostylus (Desmostylia, Mammalia). Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1078344.